2014
DOI: 10.1080/10408398.2011.638227
|View full text |Cite
|
Sign up to set email alerts
|

Instant Noodles: Processing, Quality, and Nutritional Aspects

Abstract: Noodles are one of the staple foods consumed in many Asian countries. Instant noodles have become internationally recognized food, and worldwide consumption is on the rise. The properties of instant noodles like taste, nutrition, convenience, safety, longer shelf-life, and reasonable price have made them popular. Quality factors important for instant noodles are color, flavor, and texture, cooking quality, rehydration rates during final preparation, and the presence or absence of rancid taste after extended st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 91 publications
3
114
1
9
Order By: Relevance
“…A key example of this is instant noodles; an ultra-processed ultra-processed food product which is widely available at a low cost [9]. According to the World Instant Noodles Association (WINA), 270 million servings of instant noodles are consumed worldwide each day, with 80% of total consumption in Asian countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…A key example of this is instant noodles; an ultra-processed ultra-processed food product which is widely available at a low cost [9]. According to the World Instant Noodles Association (WINA), 270 million servings of instant noodles are consumed worldwide each day, with 80% of total consumption in Asian countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that food fortification is one of the more effective strategies for targeting rural populations [53]. It is important to note that when designing intervention programs that target a specific population, cost may not be the only factor to consider, as consumers are also sensitive to the taste [54], color [55] and texture [56] of the food items involved, showing that acceptance of the fortified product is key.…”
Section: Cost Savings Associated With Food Fortificationmentioning
confidence: 99%
“…Generally, higher water absorption (weight gain) and swelling volume (volume gain) and lower cooking losses are desired characteristics for noodles (Bilgiçli 2009). Also, Gulia et al (2014) reported a positive correlation between ash content and gains in weight and volume. Insufficient water absorption could lead to hard and coarse texture, whereas excess water absorption generally produces very soft and sticky noodles (Song et al 2013).…”
Section: Resultsmentioning
confidence: 92%
“…Every year, the noodle industry supplies over 95.4 billion servings of various types of noodles, which are consumed in more than 80 countries (Gulia et al 2014). Every year, the noodle industry supplies over 95.4 billion servings of various types of noodles, which are consumed in more than 80 countries (Gulia et al 2014).…”
mentioning
confidence: 99%